Effects of Previous Exposure of Aedes aegypti (Diptera: Culicidae) Mosquitoes to Spatial Repellent Chemicals on BG-Sentinel™ Trap Catches - Salazar, Ferdinand V.; Achee, Nicole L.; Grieco, John P.; Tuntakon, Siripun; Polsomboon, Suppaluck; Chareonviriyaphap, Theeraphap (Agriculture and Natural Resources, 2012)
The use of the BG-Sentinel™ (BGS) trap as the pull component in a push-pull strategy to control Aedes aegypti mosquitoes needs to include studies on the effects of previous exposure of the mosquito to spatial repellents (the push component). The study was conducted from January 2010 to May 2011 in Pu Teuy Village, Kanchanaburi, Thailand. Aedes aegypti females were exposed to spatial repellents ([1, 1, 1-trichloro-2,2-bis (4-chlorophenyl) ethane] (DDT), metoﬂ uthrin and transﬂ uthrin) and then released within a screen house containing four BGS traps to determine the effect of the spatial repellent exposure on BGS trap capture rates from non-exposed control females. This included: (i) an immediate release experiment where females exposed during 0600–1200 hours were released at 1200 hours and (ii) a delayed release experiment where females exposed during 1200–1800 hours were released at 0530 hours the following day, thus having a recovery period of nearly 12 hours. Exposure of Ae. aegypti females to DDT or metoﬂ uthrin did not signiﬁ cantly impact BGS trap capture rates compared to non-exposed control females. However, exposure to transﬂ uthrin resulted in a signiﬁ cantly lowered number of recaptured treated versus control females in the immediate release trial but not in the delayed release one. The ﬁ ndings indicated that previous exposure of Ae. aegypti to spatial repellents has minor, short-lived impacts on the capture success with BGS traps.